CLEAR Mentoring Summit Oct. 25 - Uribes, Tom::::::::: (2013)
The second annual CLEAR Mentoring Summit 7:30 a.m.-4 p.m., Friday Oct. 25 in the North Gym atFresno State will bring educators, community organizers and business sector leaders fromthroughout the state to discuss educational and social disparities via advocacy, leadership development and mentoring.